assessment of nursing professional competencies in a tertiary level public hospital in Guanajuato, Mexico - Hernández-Pérez, Luz María; Moreno-Monsiváis, María Guadalupe; Cheverría-Rivera, Sofía (Horizonte Sanitario, 2022)
Objective: Analyze the self-assessment of the professional competencies of nurses in a tertiary care public hospital related to their work characteristics. Material and Methods: Quantitative, descriptive correlational study of 162 nursing professionals in the hospitalization services of a tertiary care public hospital, using the validated instrument “Professional competencies for nursing graduates”, with a Cronbach’s Alpha reliability of 0.97, the study complied with the stipulations of the Regulations of the General Law of Health on Research. Results: Of the nursing professionals evaluated, 77.2% were female; the predominant age range was 41-45 years with 50.6%, mostly married (44.4%). The most outstanding characteristics were seniority of 11 to 14 years (48.1 %) and a bachelor’s degree (49.4 %). The overall level of professional competencies was 164.8 (SD=11.4) out of a maximum score of 200, the ethics indicator stands out with a mean of 33.85 (SD=2.88), followed by the comprehensive care indicator with a mean of 33.33 (SD=3.22). No statistically significant relationship was found between the professional competencies of the nursing staff and the work characteristics. Conclusions. The nursing staff is perceived as competent to provide comprehensive care with ethical attachment; however, there is a demand to strengthen dimensions such as education, research and management that contribute to the continuous improvement of quality and safety in care. Keywords: Self-assessment; Competencies; Professionals; Nursing.